2011
DOI: 10.1111/j.1654-109x.2011.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation recovery of gypsum quarries: short‐term sowing response to different soil treatments

Abstract: Question: How does the sowing of native species under different soil treatments contribute to the recovery of gypsum habitats affected by quarrying in Mediterranean environments? \ud \ud Location: Mediterranean gypsum outcrops in Granada (SE Spain; 37 degrees 2' N, 3 degrees 45' W). \ud \ud Methods: We conducted an experimental sowing of native perennial species from gypsum habitats (both gypsophiles and gypsovags) considering two factors: bedding materials and surface treatments. For bedding material we used:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In this sense, the role of gypsum solutions at specific concentrations would aid seed germination of some species, being useful to select appropriate conditions to promote seedling production for restoration purposes. In particular, gypsum has been found of key importance when preparing the substrate on which to perform sowings for recovery gypsum habitats (Ballesteros et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the role of gypsum solutions at specific concentrations would aid seed germination of some species, being useful to select appropriate conditions to promote seedling production for restoration purposes. In particular, gypsum has been found of key importance when preparing the substrate on which to perform sowings for recovery gypsum habitats (Ballesteros et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Competition may also exist for nutrition or light, but the relationship differs among different species (Denslow et al, 2006;Mendoza-Hernández et al, 2014). Research indicated a very comprehensive relationship between different coexisting species; not only negative but also positive relationships were shown in different studies (Harmer et al, 2011, Ballesteros et al, 2012Zhang et al, 2013;Oliveira et al, 2014).…”
Section: The Effect Of Herbaceous Species On the Growth Of Shrubmentioning
confidence: 99%
“…In abandoned quarries or surface mines, recolonization of plants is very difficult (Ballesteros et al, 2012) because of the destruction of natural soil structure and seed bank, as well as the limitation of nutrition and water (Jim, 2001;Haritash et al, 2007). Even though technical restoration can accelerate succession, it takes decades to achieve a complex self-sustainable ecosystem (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, gypsum habitats are 58 often impacted by human disturbances such as quarrying, ploughing or grazing (AlHarthi, 2001;Mota et al, 2004;Pulido-Bosch et al, 2004;Pueyo and Alados, 2007; 60 Ballesteros et al, 2013). Therefore, recovery plans for these environments need to be addressed, and proactive measures need to be considered (Ballesteros et al, 2012(Ballesteros et al, , 62 2014, because natural succession has proved inefficient over the short term (Mota et al 2003(Mota et al , 2004Dana and Mota, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of gypsum areas has been satisfactorily approached through hydroseeding (Matesanz and Valladares, 2007), sowing (Ballesteros et al, 2012) or 66 planting (Sharma et al, 2001;Blignaut and Milton, 2005;Ballesteros et al, 2014).…”
mentioning
confidence: 99%